SYNTHESIS, STRUCTURE AND PROPERTIES OF PARTLY SUBSTITUTED OF (La,Ca)VO4: Eu3+, Er3+: UDC 546. 05' 65' 88 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Nowadays, useful materials based on lanthanides elements. Among different types of modern materials, orthovanadates are an important family of rare earth compounds and have potential applications in the fields of laser hosts, catalysts, phosphors, sensors and polarizers. The search for new rare earth ortovanadates lead to created cations of europium (EuVO4) and lanthanum (LaVO4) vanadates. In general, the orthovanadates compounds crystallize in two polymorphs, a tetragonal zircon-type structure (space group: I41/amd, Z = 4) and a monoclinic monazite-type (space group: P21/n, Z = 4). Compounds with small rare-earth cations, such as EuVO4 have zircone-type structure. Compounds with a large rare-earth cation, such as LaVO4, will experience zircone to monazite phase transitions. However, zircon-type structure of LaVO4 compound is metastable. The aim of this work was to synthesize and investigating their X-Ray and structural features, morphological and physical properties of Lа1-xErx/4Eux/4Cax/2VO4 (0 ≤ x ≤ 0.2) compounds.The Lа1-xErx/4Eux/4Cax/2VO4 (0 ≤ x ≤ 0.2) samples were prepared by aqueous nitrate-citrate gel-sol synthesis route taking citric acid (CA) as a complexing agent. Infrared spectra (IR) of the samples were recorded on PerkinElmer IR spectrometer using the KBr pellet method in the range 1400–400 cm-1. The phase composition and crystal lattice parameters were determined using x-ray diffractometers DRON-3М (CuKa-radiation with a Ni filter) and DRON-7 (FeKa-radiation with a Mn filter). The diffraction patterns were taken at a step of 2 deg./min. The microstructure of the compounds obtained was studied with a scanning electron microscope (SEM) Hitachi S – 2400. The pattern fits of La0.9Er0.025Eu0.025Ca0.05VO4, La0.8Er0.05Eu0.05Ca0.1VO4 compounds well with monoclinic monazite-type, and La0.65Er0.1Eu0.1Ca0.15VO4, La0.5Er0.15Eu0.15Ca0.2VO4 samples crystallized in a tetragonal zircon-type structures. The photoluminescence spectra contain wide bands of matrix emission and narrow lines caused by f-f transitions in the RE3+ ions.
Keywords: gel-sol method; orthovanadates; rare earth element; luminescence